The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1002/esp.3782
|View full text |Cite
|
Sign up to set email alerts
|

Near‐bed shear stress, turbulence production and dissipation in a shallow and narrow tidal channel

Abstract: Near-bed, highly resolved velocity profiles were measured in the lower 0.03 m of the water column using acoustic Doppler profiling velocimeters in narrow tidal channels in a salt marsh. The bed shear stress was estimated from the velocity profiles using three methods: the log-law, Reynolds stress, and shear stress derived from the turbulent kinetic energy (TKE). Bed shear stresses were largest during ebbing tide, while near-bed velocities were larger during flooding tide. The Reynolds stress and TKE method gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…As seen in other studies, all three methods produced results with similar patterns, but peak magnitudes showed considerable differences ( e.g. , ( Kim et al, 2000 ; Sherwood, Lacy & Voulgaris, 2006 ; Pieterse et al, 2015 )). Because the covariance method is less affected by local conditions ( e.g.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…As seen in other studies, all three methods produced results with similar patterns, but peak magnitudes showed considerable differences ( e.g. , ( Kim et al, 2000 ; Sherwood, Lacy & Voulgaris, 2006 ; Pieterse et al, 2015 )). Because the covariance method is less affected by local conditions ( e.g.…”
Section: Methodssupporting
confidence: 81%
“…Multiple methods are commonly used and compared, as methods can be biased by local conditions such as waves, stratification, and bedforms ( e.g. , Sherwood, Lacy & Voulgaris, 2006 ; Pieterse et al, 2015 ). The logarithmic profile method assumes a logarithmic velocity profile using the von Karman-Prandtl equation.…”
Section: Methodsmentioning
confidence: 99%
“…Turbulence-related parameters were derived from the rotated fluctuating velocity components. The linear elements of the stress tensor, corresponding to the interaction between the horizontal and vertical components, were used for calculating the shear stresses at the sampling location (Pieterse et al 2015):…”
Section: Turbulence Measurementsmentioning
confidence: 99%
“…By default, the Vectrino profiler reports velocities along a 3.5 cm long profile ranging from 4 to 7.5 cm below the emitter. The profiler has already been used in situ to characterize the fluid flow at high resolution in tidal boundary layers [ Pieterse et al ., ; Wengrove and Foster , ]. In a recent study, Brand et al .…”
Section: Introductionmentioning
confidence: 99%
“…By default, the Vectrino profiler reports velocities along a 3.5 cm long profile ranging from 4 to 7.5 cm below the emitter. The profiler has already been used in situ to characterize the fluid flow at high resolution in tidal boundary layers [Pieterse et al, 2015;Wengrove and Foster, 2014]. In a recent study, Brand et al [2016] noticed that flow and turbulence statistics are most reliable in a rather narrow range which corresponds the point of maximum overlap sampled by the different receivers (this so-called sweet spot is located approximately 5 cm below emitter), while mean velocities are trustworthy over a 2 cm long vertical profile ranging from 4 to 6 cm below the emitter.…”
Section: Introductionmentioning
confidence: 99%